2016
DOI: 10.1016/j.rbre.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Familial autoimmunity and polyautoimmunity in 60 Brazilian Midwest patients with systemic sclerosis

Abstract: From the high prevalence of coexisting autoimmune diseases found in SSc patients, we stress the importance of the concept of shared autoimmunity, in order to promote a continued vigilance and promptly diagnose other possible autoimmune disease in patients, or in their kin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous studies have documented that autoimmune diseases often co-aggregate within families. Several studies also found an increased risk of other autoimmune disease in family members of SSc patients [ 9 11 , 23 , 24 , 34 , 35 ]. A relatively large study investigating 4612 first-degree relatives of 1071 SSc probands found that the most prevalent autoimmune diseases among first-degree relatives of SSc patients were hypothyroidism, rheumatoid arthritis, hyperthyroidism, and SLE [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that autoimmune diseases often co-aggregate within families. Several studies also found an increased risk of other autoimmune disease in family members of SSc patients [ 9 11 , 23 , 24 , 34 , 35 ]. A relatively large study investigating 4612 first-degree relatives of 1071 SSc probands found that the most prevalent autoimmune diseases among first-degree relatives of SSc patients were hypothyroidism, rheumatoid arthritis, hyperthyroidism, and SLE [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Familial associations between two diseases are good indications of shared genetic susceptibility. Evidence of co‐occurrence of autoimmune diseases (ADs) within families of IIM (familial autoimmunity) is either from small‐scale family‐based studies of patients with IIM or other ADs [ 10 , 11 , 12 , 13 , 14 ] or from large‐scale family‐based studies based primarily on patients with other ADs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Some of these studies observed higher frequencies of rheumatoid arthritis (RA) in families of IIM [ 10 ], or reported significant familial associations of RA, systemic lupus erythematosus (SLE), systemic sclerosis (SSc), type 1 diabetes mellitus (T1DM) and autoimmune thyroid diseases (AITD) with IIM [ 11 , 17 , 19 , 21 , 24 ] while other studies did not support familial associations for RA, Sjögren's syndrome (SS), SSc, multiple sclerosis (MS), inflammatory bowel diseases (IBD), coeliac disease (CeD) and myasthenia gravis (MG) with IIM [ 11 13 , 15 , 16 , 18 , 20 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a Brazilian study conducted on 60 consecutive patients with scleroderma, polyautoimmunity was found in 43.3% of patients and the most frequent AID observed was Hashimoto's thyroiditis (53.8%) followed by Sjögren's syndrome (38.5%), inflammatory muscle disease (11.5%), antiphospholipid syndrome (7.7%) and RA (3.8%). The majority of patients had only one concurrent AID (73.08%).…”
mentioning
confidence: 99%